Analisis Daya Tampung Beban Pencemaran Sungai Siak Bagian Hilir Menggunakan Pendekatan Water Quality Analisys Simulation Program (Wasp) Versi 7.3 (Wilayah Kabupaten Siak) - Handrianti, Pipi; Suprayogi, Imam; Andesgur, Ivnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Siak River is one of the largest river in Indonesia that has national concern and be included as national strategic river. Siak River has widely utilized by the surrounding population, but in recent times, the Siak River Basin including its critical downstream watershed in Siak regency, occuring the decrease of river water flow and quality, triggered by increased activity along the river basin which is dominated by plantation activities. In this research, the Siak Siam Load Capacity Analysis of Siak downstream in Siak district using WASP7.3 model with 14 segments for each BOD parameters in the minimum discharge simulation is 151 m3 / sec followed by reducing the pollution load according to the standard quality of class II. Reductions of pollution load are 75% of BOD parameter, so that attaining the standard quality of class II. The value of DTBP after the reduction for the pollution load of BOD are 12.134,95 kg / day respectively. Siak watershed downstream of Siak district is recommended into the designation of class II according to Government Regulation No. 82/2001 on Water Quality Management and Water Pollution Control.Keywords: Pollution Load, WASP7.3, Pollution Load Reduction, DTBP